Minor straw return enhances net income in a maize-wheat rotation system - Li, Juan; Guo, Zhen; Ye, Shenglan (Frontiers in Environmental Science, 2024)
Straw returning to the field is a common agricultural practice in China. Nevertheless, in the maize-wheat rotation system of the semi-arid region in Northwest China, it is essential to investigate the optimal approach for coupling straw return and fertilization in order to enhance soil quality and crop yield. A field trial conducted in the semi-arid region of northwest China from 2019 to 2021 examined eight different combinations of straw return and fertilization rates. The results indicated that while straw return had minimal impact on soil total nitrogen in the 0–60 cm layer, it did increase soil available phosphorus and potassium in the 0–40 cm layer. Additionally, all straw return treatments notably improved soil organic matter and humus content compared to the untreated control (CK). Specifically, applying N and P fertilizers in combination with returning 1/3 of the straw (NP+1/3S) produced in that season significantly boosted soil organic matter and humus content compared to the CK. Moreover, the NP+1/3S treatment led to a substantial enhancement in the grain yield of wheat and maize, as well as their yield components, including an increase in the number of ears/spikes per square meter, the number of grains per ear/spike, and the 100 or 1000-grain weight. The results may be attributed to a combination of factors, including improved nutrient availability, enhanced soil structure, and increased microbial activity due to the incorporation of straw. Economic analysis showed that NP+1/3S had the highest production to investment ratio (ROI), indicating its potential suitability for the region. This study highlights the significance of carefully selecting combinations of straw return and fertilization to maximize soil fertility, crop yield, and economic benefits in agricultural systems.